ANALISIS PENGARUH ZAKAT PRODUKTIF TERHADAP KESEJAHTERAAN DAN PENDAPATAN USAHA MUSTAHIK MENGGUNAKAN METODE CIBEST - Putri, Yuniar Mualidyana; Paksi, Girindra Mega (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Various efforts and policies that have been implemented have not had a significant and effective impact on overcoming the problems of poverty and wealth inequality. Productive zakat has the potential to alleviate poverty through financial support to micro businesses to improve their welfare. This research aims to analyze the influence of productive zakat on improving the economy and welfare of mustahik using the CIBEST method. This research uses a descriptive quantitative approach with CIBEST model analysis techniques and statistical tests of research instruments (Validity, Reliability and Paired T-Test) to look for changes in the level of welfare in 31 mustahik LAZ YASA, LAZNAS YDSF and LAZNAS DT Peduli Malang City. The results of this research concluded that productive zakat has a positive effect on the level of welfare of mustahik. The productive zakat program has succeeded in improving the welfare of mustahik in Malang City, both materially and spiritually. Mustahik experienced an increase in average income of 75%, while for spiritual mustahik it increased by 8.53%. The number of mustahik in the prosperous category increased by 13%, while in the material poor category it decreased by 13%, in the spiritual poor and absolute poor categories by 0%.